Computed tomography and positron emission tomography/computed tomography surveillance after combined modality treatment of supradiaphragmatic Hodgkin lymphoma: a clinical and economic perspective. Issue 10 (October 2013) - Patel, Vatsal; Buckstein, Michael; Perini, Rodolfo; Hill-Kayser, Christine; Svoboda, Jakub; Plastaras, John P.
Abstract We studied the clinical benefits of radiological imaging, in the follow-up of patients after combined modality treatment for stage I/II classical supradiaphragmatic Hodgkin lymphoma (HL). Imaging data were collected for 78 adults treated during 1996–2008. Median follow-up was 4.6 years. Six of the nine relapses were detected clinically. On average, 31 imaging studies/patient were performed, with an estimated cost of 12 608/patient. Chest computed tomography (CT) scans accounted for 25%, abdominopelvic CT scans 41% and positron emission tomography (PET) or PET/CT scans 22% of this expense. Only one patient recurred infradiaphragmatically. The estimated radiation dose from imaging was 399 mSv and 229 mSv per patient, in relapse and non-relapse groups, respectively. CT scans contributed over 80% of the imaging radiation exposure. The routine use of CT scans in the surveillance of patients with HL after curative treatment adds to healthcare costs and total body radiation exposure with a low yield. History and physical examination remain effective tools for the follow-up of patients.